Implementation of water energy food-health nexus in a climate constrained world: a review for South Africa - Mutanga, Shingirirai S.; Mantlana, Brian K.; Mudavanhu, Shepherd; Muthige, Mavhungu S.; Skhosana, Felix V.; Lumsden, Trevor; Naidoo, Sasha; Thambiran, Tirusha; John, Juanette (Frontiers in Environmental Science, 2024)
In recent years, the Water-Energy-Food (WEF) nexus has gained significant attention in global research. Spatial inequality in water-energy-food security (WEF) and its impact on public health and how this is affected by climate change remains a grand adaptation challenge. South Africa is extremely vulnerable and exposed to the impacts of climate change due to its socio-economic and environmental context. While alternative nexus types have garnered interest, this paper pioneers an extension of the conventional WEF framework to encompass health, giving rise to the Water-Energy-Food-Health (WEF-H) nexus. Despite a plethora of WEF nexus studies focused on South Africa, a substantial knowledge gap persists due to the lack of a comprehensive overview of the enablers and barriers to realizing the WEF-H nexus. South Africa boasts diverse policies related to water, energy, food, and health; however, their alignment remains an ongoing challenge. This study seeks to bridge this critical gap by conducting an exhaustive review of existing literature. Its primary aim is to delve into the intricate mechanisms that either facilitate or impede the actualization of the WEF-H nexus in South Africa. By synthesizing insights from a wide array of literature sources, this research strives to illuminate the challenges and opportunities stemming from the integration of health considerations into the established WEF nexus framework. This exploration holds immense significance, not only for unraveling the multifaceted interactions between these pivotal sectors but also for guiding policy development and decision-making processes in South Africa towards a more holistic and sustainable approach to resource management.